Time course of qMRI, functional, and strength measurs. - Susanne S. Rauh (21192252) (2025)
Line plots showing the time course over the years since diagnosis. Each line represents an individual with LGMD-R9 and the same colors show the same participant. A. FF in the global thigh and global leg. B. FF in the most and least fat-replaced thigh and leg muscles (AM, VM, GM, TA). C. Functional measures NSAD and FVC. D. Strength tests for knee extension and ankle plantarflexion. The predicted strength is shown. AM, adductor magnus; VM, vastus medialis; GM, gastrocnemius medialis; TA, tibialis anterior; FF, fat fraction; FVC, forced vital capacity; NSAD, North Star Assessment for Limb-Girdle Type Muscular Dystrophies.